THE INFLUENCE OF WORK DISCIPLINE, ORGANIZATIONAL CLIMATE AND ORGANIZATIONAL CULTURE ON ORGANIZATIONAL COMMITMENT THROUGH JOB SATISFACTION AS AN INTERVENING VARIABLE IN THE BPJS EMPLOYMENT OFFICE, BATAM CITY - Dix Wendy Saragih; Indrayani; Muammar Khaddafi; Chablullah Wibisono; Mohamad Gita Indrawan (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2023)
The purpose of this research is to determine and analyze the influence of work discipline, organizational climate and organizational culture on organizational commitment through job satisfaction at the Batam City BPJS Employment Office. This type of research uses an associative causality design. Data was collected using a questionnaire and distributed to 115 respondents. Statistical data analysis uses SEM-PLS (Structural Equation Modeling Partial Least Square) and uses path analysis to test relationship patterns that reveal the influence of variables on other variables, both direct and indirect. The research results show that Work Discipline directly has a positive and significant effect on Job Satisfaction with P-Values ​​of 0.002 < 0.05. Work Discipline directly has a positive but not significant effect on organizational commitment with P-Values ​​of 0.701 > 0.05. Organizational Climate directly has a positive and significant effect on Job Satisfaction with P-Values ​​of 0.041 > 0.05. Organizational Climate directly has a positive and significant effect on Organizational Commitment with P-Values ​​of 0.010 > 0.05. Organizational Culture directly has a positive and significant effect on Job Satisfaction with P-Values ​​of 0.008 <0.05. Organizational Culture directly has a positive and significant effect on Organizational Commitment with P-Values ​​of 0.006 > 0.05. Job Satisfaction directly has a positive and significant effect on Organizational Commitment with P-Values ​​of 0.000 <0.05. Job Satisfaction mediates the influence of Work Discipline on Organizational Commitment with p-values ​​of 0.411 > 0.05. Job Satisfaction mediates the influence of Organizational Climate on Organizational Commitment with P-values ​​of 0.007 < 1.234. Job Satisfaction mediates the influence of Organizational Culture on Organizational Commitment with p-values ​​of 0.004 < 0.05.